1996
DOI: 10.1152/ajpgi.1996.271.3.g387
|View full text |Cite
|
Sign up to set email alerts
|

Action potential generation in the small intestine of W mutant mice that lack interstitial cells of Cajal

Abstract: The small intestine of W/Wv mice lacks both the network of interstitial cells of Cajal (ICC), associated with Auerbach's plexus, and pacemaker activity, i.e., it does not generate slow-wave-type action potentials. The W/Wv muscle preparations showed a wide variety of electrical activities, ranging from total quiescence to generation of action potentials at regular or irregular frequency with or without periods of quiescence. The action potentials consisted of a slow component with superimposed spikes, preceded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 0 publications
12
83
1
1
Order By: Relevance
“…1B). These results are similar to those reported in previous studies (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002Nakagawa et al, 2005).…”
Section: Immunohistochemical Studiessupporting
confidence: 93%
See 2 more Smart Citations
“…1B). These results are similar to those reported in previous studies (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002Nakagawa et al, 2005).…”
Section: Immunohistochemical Studiessupporting
confidence: 93%
“…We have previously reported that spontaneous rhythmic contractions are observed in the proximal colon of Ws/Ws rats, where there is a deficiency of both ICC in the myenteric region (ICC-MY) and of ICC-SM (Yoneda et al, 2001). Furthermore, it has been reported that smooth muscle preparations of the small intestine (duodenum, jejunum or ileum) of W/W V mutant mice show a variety of electrical activities (Malysz et al, 1996), longitudinal cyclic contractions (Daniel et al, 2002) and distension-induced peristalsis . In the small intestine of W/W V mutant mice, while ICC-MY are absent, the ICC of the deep muscular plexus region (ICC-DMP) are present (Malysz et al, 1996;Takayama et al, 2001Takayama et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the musculature can be directly activated by distension without mediation of enteric nerves. Activity in the presence of TTX or atropine was higher in WW v mice than in control mice, possibly because the musculature itself is depolarized and, hence, more excitable (Malysz, Thuneberg, Mikkelsen & Huizinga, 1996). With identical frequencies, the action potentials were synchronized and apparent propagation was observed ( Fig.…”
Section: Control Micementioning
confidence: 93%
“…ICC function as pacemaker cells in the gastrointestinal tract and may also modulate enteric neurotransmission (15,28,29). Spontaneous mutations at the white spotting locus, which encodes the c-kit receptor or the Steel locus, which encodes SF, are associated with disruption of the ICC network located at the myenteric plexus region (ICC-MY) of the small intestine and the functional loss of the spontaneous electrical slow wave and contractile activity (23,24,34,35). SF activation of c-kit is also necessary to maintain ICC, because the administration of neutralizing c-kit antibody results in the subsequent disappearance of ICC (21,30).…”
mentioning
confidence: 99%